2016
DOI: 10.1021/acs.analchem.6b04099
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Metoprolol in Human Biofluids and Pharmaceuticals via Ion-Transfer Voltammetry at the Nanoscopic Liquid/Liquid Interface Array

Abstract: Metoprolol (MTP) is one of the most widely used antihypertensive drugs yet banned to use in sport competition. Therefore, there has been an increasing demand for developing simple, rapid, and sensitive methods suited to the identification and quantification of MTP in human biofluids. In this work, ultrathin silica nanochannel membrane (SNM) with perforated channels was employed to support nanoscale liquid/liquid interface (nano-ITIES) array for investigation of the ion-transfer voltammetric behavior of MTP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Micro-ITIES arrays were also modified with mesoporous silica channels prepared ex-situ by a Stöber-like method [36]. The vertically aligned channels obtained have demonstrated their potential for analytical applications [37][38][39][40]. We investigated here the adsorption of silica nanoparticles onto the ITIES and their impact on the electrochemical transfer behaviour of ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-ITIES arrays were also modified with mesoporous silica channels prepared ex-situ by a Stöber-like method [36]. The vertically aligned channels obtained have demonstrated their potential for analytical applications [37][38][39][40]. We investigated here the adsorption of silica nanoparticles onto the ITIES and their impact on the electrochemical transfer behaviour of ions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ic= Iw-Ig/Ig (2) Where Ig and Iw are the intensity ratio of the acceptor and donor before and after treated with glucose solution. As EDC mediated all the amine groups on the surface of GBP-Rluc with the carboxylic groups on the surface of CdTe, the bioconjugation process is non-site specific [23,30], the excess amount of either GBP-Rluc or QDs may affect the sensitivity of this sensor.…”
Section: Assay Optimizationmentioning
confidence: 99%
“…Body fluids such as urine [2][3][4], sweat [5][6][7][8] and tear [9][10][11][12] thus have been widely used as testing samples. It has been found that tear glucose level is around 5 times higher in diabetes patients than in normal people and the tear glucose has been identified to have a positive correlation with the blood glucose based on previous research [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nanoporous gold electrodes have been employed for the detection of DNAs in diluted biofluids . SNM modified electrodes have also illustrated excellent antifouling ability and allowed the direct detection of a variety of targets in complex samples and rat brain with high sensitivities . Our previous study shows that the SNM modified carbon fiber microelectrode (SNM/CFME) can work stably in rat brain up to 2 h .…”
Section: Introductionmentioning
confidence: 99%